Trust Your Instincts: The Relationship Between Intuitive Decision Making And Happiness - Stevenson, Simone S.; Hicks, Richard E. (European Scientific Journal, ESJ, 2016)
Epstein (1994; 2003) proposed that there are two cognitive information processing systems that operate in parallel: the intuitive thinking style and the rational thinking style. Decisional fit occurs when the preferred thinking style is applied to making a decision and research has shown that this fit increases the value of the outcome of a decision. Additionally, decisional fit leads to less regret, even when post hoc evaluations show the decision to be incorrect. It has not yet been determined whether decisional fit correlates with greater happiness and hence, the purpose of the current study was to investigate the difference between styles of thinking, styles of decision making and the impact of decisional fit on happiness scores. Individual differences in thinking and decision style were measured using an online interactive questionnaire (N = 100), and an ANOVA, hierarchical multiple regression, and a series of t-tests, were used to investigate the relationship between thinking style, decision style, decisional fit, and happiness, thereby addressing a gap in the existing literature. The major findings from the current study show that intuitive thinking has a strong positive correlation with happiness; that intuitive thinkers are more likely to utilize intuitive decisional style, than rational thinkers; and that when both rational and intuitive thinkers experienced decisional fit, higher ratings of happiness were reported. Explanations and recommendations for future studies are outlined in the discussion.